p-Hydroquinone-metal compounds: Synthesis and crystal structure of two novel VV-p-hydroquinonate and VIV-p-semiquinonate species - Tolis, Vagelis; Gramlich, Volker; Drouza, Chryssoula (My University, 2002)
Reaction of the p-hydroquinone derivative H2Na4bicah·4H2O with either VIVOSO4·3H2O and NaVVO3 in equivalent quantities or with NaVVO3 yields the tetranuclear VIVO2+ macrocycle-semiquinonate compound Na6{(VIVO)4-(μ2-O) 2[μ2-bicas·(-5)-N,O,O,O]2}·Na 2SO4·20H2O (1·Na2SO4·20H2O) and the dinuclear cis-VVO2+-hydroquinone species Na4{(VVO2)2[μ2- bicah(-6)-N,O,O,O]}·11H2O (2·11H2O) respectively. Compounds 1·Na2SO4·20H2O and 2·11H2O were characterized by X-ray structure analysis and ab initio calculations
Keywords: Hydroquinone; Quinone; Quinone--Derivatives; Chemical reactions; Chemical structure